2017
DOI: 10.7903/cmr.17430
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Corporate Social Responsibility and Employer Attractiveness in Egypt: The Moderating Effect of the Individual’s Income

Abstract: Corporate social responsibility activities can generate many forms of competitive advantage. Employer attractiveness, among others, is one them. Simultaneously, the global talent shortage and the national labor market dynamics render talent attraction a big challenge for organizations in Egypt. The relationship between corporate social responsibility and employer attractiveness was neither tested in Egypt, nor moderated by the individual's income. The main motivation behind this study is to close these gaps. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
(92 reference statements)
2
11
0
Order By: Relevance
“…Njeri (2014) added that the periodic and continuous assessment of the internal control structure to make sure that it is working as intended is important to timely correct any weaknesses of the internal control and avoid their reoccurrence in the future, thus monitoring positively affects the financial performance (Njeri, 2014). This agrees with many previous studies such as Ibrahim et. al., (2017), Mwangi and Muturi (2018), Muraleetharan (2011) and Etengu and Amony (2016) that concluded that monitoring has a positive and significant impact on the financial performance.…”
Section: H 1 : Higher Internal Control Structure Quality Positively Impacts the Financial Performance Of Firms Listed In The Egyptian Stosupporting
confidence: 94%
See 3 more Smart Citations
“…Njeri (2014) added that the periodic and continuous assessment of the internal control structure to make sure that it is working as intended is important to timely correct any weaknesses of the internal control and avoid their reoccurrence in the future, thus monitoring positively affects the financial performance (Njeri, 2014). This agrees with many previous studies such as Ibrahim et. al., (2017), Mwangi and Muturi (2018), Muraleetharan (2011) and Etengu and Amony (2016) that concluded that monitoring has a positive and significant impact on the financial performance.…”
Section: H 1 : Higher Internal Control Structure Quality Positively Impacts the Financial Performance Of Firms Listed In The Egyptian Stosupporting
confidence: 94%
“…Egyptian companies need to focus on tools to improve their financial performance to solve the current financial difficulties they face (Mohamed, 2020;Ibrahim, 2017). However, many companies in Egypt are suffering critical financial problems due to the severe inflation, financial and economic circumstances (Mohamed,2020;Ibrahim, 2017).…”
Section: -Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This image is created as a result of cognitive and affective evaluation shaped through the prism of knowledge, feelings, previous experiences or opinions of other entities (labour market participants) heard in whole or in part (Ibrahim, 2017 The image of an organisation translates into attitudes towards the organisation, while on the other hand, the analysis of attitudes enables the identification of the image. An attitude is defined as: a permanent system of positive or negative assessments, emotional feelings and pro or contra-tendencies to act in relation to a certain social object (Soborski, 1987, pp.…”
Section: Kienzlermentioning
confidence: 99%